"A picture is worth a thousand words": Reverse image lookup and digital library assessment. (20th June 2017) - Thompson, Santi; Reilly, Michele
Abstract : This brief communication builds on the application of content‐based image retrieval (CBIR) and reverse image lookup (RIL), a graduated form of CBIR, as assessment tools for digital library image reuse. It combines literature on the definition, history, usefulness, and limitations of RIL and includes a brief analysis of the 4 published digital library image reuse assessment case studies. In its conclusion, the communication paper proposes that RIL offers benefits for digital library managers in the assessment of their collections.